New Media: Analisis Konten Etika Komunikasi Publik Humas Pemerintahan pada Akun X @Kemkominfo - Lubis, M Akbar Affandi; Sembiring, M Alfin Eraninka; Fahirah, Raisah; Perangin Angin, Dwi Israfi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to analyze the ethics of public relations communication in the government on the X @Kemkominfo account in analyzing the content of message delivery to the public. The type of research used is descriptive qualitative, the primary data source focuses on the content of the account which is then analyzed using content analysis. The results show that the government account @Kemkominfo has not yet implemented communication ethics through social media X. This is due to the dislike of netizens towards the arrogant nature of the message responses on an account that should represent part of Indonesia. In addition, the language style used by the admin on the X @Kemkominfo account tends to use slang and is informal.